Imaginarios culturales y representaciones visuales del sincretismo religioso en murales con la temática del Niño Rey de Reyes, en el Cantón Riobamba, Barrio de Santa Rosa en el periodo académico mayo 2021- septiembre 2021 - Ramos Moyota, David Alexander (2022)
Traditions gradually disappear due to foreign influence or ignorance of the subject. This situation has resulted in the loss of respect and, at the same time, cultural, ancestral, and religious interest, thus weakening the sense of identity. Furthermore, the misuse of public spaces generates visual contamination that affects several aspects of human life. It is not only the visual discomfort that stains walls that deteriorate buildings. Additionally, expletives expressed with words or images affect the passersby and create a wrong impression of the place. The investigation entitled: “Cultural imaginaries and visual representations of religious syncretism in walls paintings with the theme Niño Rey de Reys in Santa Rosa neighborhood of Riobamba, during May 2021 to September 2021.” The study objective is to represent original cultural imaginaries in wall paintings, focused on “Niño Rey de Reyes” characters. The applied methodology has a qualitative-quantitative approach due to the exhaustive literature review and the application of quantitative data collection instruments. Likewise, the research is non-experimental since there is no manipulation of variables. Santa Rosa market, located in Riobamba town, was the place to apply tools and materialize cultural imaginaries. As an essential part of the research development, materializing a mural within the market facilities was considered vital: from the sketching stage to the delivery of the work.